2013
DOI: 10.4067/s0718-95162013005000013
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value, flavonoid content and radical scavenging activity of the truffle (Terfezia boudieri Chatin)

Abstract: Abstract:In this study, the amounts of dry matter, moisture, crude ash, protein, fat and organic matter in T. boudieri were determined to be 89. 75, 10.25, 7.80, 20.13, 3.45 and 81.95% of the dry weight, respectively. The contents of mineral were: macronutrients (mg/g, dry wt) K 63.8, Ca 0.27 and Na 0.2; micronutrients (mg/kg, dry wt) Fe 1455.0, Zn 42.5, Mn 15.8 and Cu 30.1. Toxic elements such as Pb, Ni, Cd and Co concentrations were found to be under the detection limit of the used metod. The distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…Locally, it has an acceptable flavor and of highly nutritive seasonal food. Akyüz M. (2013) found that desert truffle (DT) is rich in linoleic, oleic and palmitic acids, and rich in flavonoids that make it showing a high free radical scavenging activity. In a different study, there was a correlation between antioxidant and antiradical activities of dried desert truffles from four different Middle Eastern countries and phenolic contents (Al-Laith, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Locally, it has an acceptable flavor and of highly nutritive seasonal food. Akyüz M. (2013) found that desert truffle (DT) is rich in linoleic, oleic and palmitic acids, and rich in flavonoids that make it showing a high free radical scavenging activity. In a different study, there was a correlation between antioxidant and antiradical activities of dried desert truffles from four different Middle Eastern countries and phenolic contents (Al-Laith, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…When the groups were compared in terms of concentration, the highest level of free radical scavenging effect at the group, to which we added a 100 μL sample, was seen at T. boudieri with 8.00% (Table 2). It seems that the radical scanvenging activity of T. boudieri might be different than what was expressed in an earlier published report [9,12,17,23,[37][38]. Bioactive compounds and antioxidant activity of mushrooms depend on its relation with the strain/type, the ascocarp size, harvest time, host plant, and the ecocystems.…”
Section: Discussionmentioning
confidence: 75%
“…The amount of TPC in T. boudieri extracts was determined according to the F-C procedure described by Akyüz (17). A stock solution of 25 mg/ml of each extract was prepared.…”
Section: Total Phenolic Content (Tpc) By Folin-ciocalteu Methodsmentioning
confidence: 99%
“…Modern medicine rediscovered ancient super foods, as a growing evidence that mushrooms (such as White button, Shiitake, Maitake, portabella, Reishi, Turkey Tail) are among the potentially positive foods for cancer fighting and prevention (15). Previous research on Terfezia boudieri reported a remarkable antibacterial, antioxidant, and radical scavenging activities of flavonoids rich extract of this truffle (16,17).…”
Section: Introductionmentioning
confidence: 99%